Quantitative optical coherence tomography angiography of vascular abnormalities in the living human eye - Jia, Yali; Bailey, Steven T.; Hwang, Thomas S.; Mcclintic, Scott M.; Gao, Simon S.; Pennesi, Mark E.; Flaxel, Christina J.; Lauer, Andreas K.; Wilson, David J.; Hornegger, Joachim; Fujimoto, James G.; Huang, David (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Retinal vascular diseases are important causes of vision loss. A detailed evaluation of the vascular abnormalities facilitates diagnosis and treatment in these diseases. Optical coherence tomography (OCT) angiography using the highly efficient split-spectrum amplitude decorrelation angiography algorithm offers an alternative to conventional dye-based retinal angiography. OCT angiography has several advantages, including 3D visualization of retinal and choroidal circulations (including the choriocapillaris) and avoidance of dye injection-related complications. Results from six illustrative cases are reported. In diabetic retinopathy, OCT angiography can detect neovascularization and quantify ischemia. In age-related macular degeneration, choroidal neovascularization can be observed without the obscuration of details caused by dye leakage in conventional angiography. Choriocapillaris dysfunction can be detected in the nonneovascular form of the disease, furthering our understanding of pathogenesis. In choroideremia, OCT's ability to show choroidal and retinal vascular dysfunction separately may be valuable in predicting progression and assessing treatment response. OCT angiography shows promise as a noninvasive alternative to dye-based angiography for highly detailed, in vivo, 3D, quantitative evaluation of retinal vascular abnormalities.
Keywords: optical coherence tomography angiography; ophthalmic imaging; ocular circulation